Perspektif Siswa terhadap Gerakan Literasi Sekolah di Sekolah Dasar - Pertiwi, Andin Julita; Permadanti, Rengganis Amelia Citra; Wulandari, Tri; Aji, Prasetyo Wahyu; Saputri, Sulis Andreani (Elementary Education Journal, 2023)
Background: The School Literacy Movement in Indonesia can be said to be low compared to other countries based on PISA research. This study aims to determine students' perceptions of the School Literacy Movement at SD Al Islam 2 jamsaren Method: This study uses qualitative methods with a phenomenological approach. Informants obtained in this study amounted to 4 people consisting of class VI students using the Non-Probability sampling technique. This research was conducted by collecting the four informants to a place that had been determined from the start with a questionnaire guide Result: the description of students' perceptions of the school literacy movement was based on a questionnaire given by the researcher. Implication: Based on the results of the questionnaire given to the informants, it was found that they did not fully understand the meaning of literacy, but for a good level of knowledge in reading literacy books. It is hoped that the results of this study can be used by teachers to find suitable strategies for increasing the literacy movement in schools Novelty: The present study revealed the implementation of literacy in elementary school comprehensively.